Self-management approaches for osteoarthritis in the hand: a 2×2 factorial randomised trial. Issue 1 (9th October 2013) - Dziedzic, Krysia; Nicholls, Elaine; Hill, Susan; Hammond, Alison; Handy, June; Thomas, Elaine; Hay, Elaine
Abstract : Background: Osteoarthritis is the leading cause of disability in older adults. Evidence of effectiveness for self-management of hand osteoarthritis is lacking. Methods: In this randomised, factorial trial, we evaluated the effectiveness of joint protection versus no joint protection, and hand exercise versus no hand exercise in adults, 50 years of age or older, with hand osteoarthritis. Following a population survey (n=12 297), eligible individuals were randomly assigned (1:1:1:1) to: leaflet and advice; joint protection; hand exercise; joint protection plus hand exercise. Joint protection and hand exercises were delivered by nine occupational therapists, over four group sessions. The primary outcome was the OARSI/OMERACT responder criteria at 6 months. Outcomes were collected blind to allocation (3, 6, 12 m). Analysis was by intention to treat. Results: Of 257 participants randomised (65:62:65:65) (mean age (SD) 66 years (9.1); female 66%) follow-up was 85% at 6 m (n=212). Baseline characteristics and loss to follow-up were similar between groups. There were no reported treatment side effects. At 6 m 33% assigned joint protection were responders compared with 21% with no joint protection (p=0.03). Of those assigned hand exercises, 28% were responders compared with 25% with no exercises (n.s.). Differences in secondary outcomes were not statistically significant, except for improvement in pain self-efficacy with joint protection (3 m p=0.002; 6 m p=0.001; 12 m p=0.03). Conclusions: These findings show that occupational therapists can support self-management in older adults with hand osteoarthritis, and that joint protection provides an effective intervention for medium term outcome. (Funded by the Arthritis Research UK ISRCTN 33870549 ).